Impact of reductive tricuspid ring annuloplasty on right ventricular size, geometry and strain in an ovine model of functional tricuspid regurgitation. (4th July 2022) - Iwasieczko, Artur; Malinowski, Marcin; Solarewicz, Monica; Bush, Jared; MacDougall, Brian; Rausch, Manuel; Timek, Tomasz A
Abstract: OBJECTIVES: Reductive ring annuloplasty of the tricuspid annulus represents the contemporary surgical approach to functional tricuspid regurgitation (FTR). We set out to investigate the influence of moderate reductive tricuspid ring annuloplasty on tricuspid regurgitation and right ventricular (RV) size, geometry and strain in an ovine model of chronic FTR. METHODS: Eight healthy Dorsett male sheep (62.8 + 2kg) underwent a left thoracotomy for placement and tightening of pulmonary artery band to at least double proximal pulmonary artery blood pressure. After 8 weeks of recovery, animals underwent sternotomy, epicardial echocardiography and sonomicrometry crystal implantation. Six crystals were placed around tricuspid annulus and 13 on RV free wall epicardium along 3 parallels defining 3 wall regions (basal, mid and lower) and 1 on the RV apex. All animals underwent beating heart implantation of 26 mm MC3 annuloplasty ring during a second cardiopulmonary bypass run after baseline data acquisition. Simultaneous haemodynamic, sonomicrometry and echocardiography data were acquired at Baseline and after reductive tricuspid ring annuloplasty. RESULTS: Implantation of reductive ring annuloplasty resulted in 47 ± 7% annular area reduction (996 ± 152 mm vs 516 ± 52 mm 2, P  = 0.0002) and significantly decreased RV end-diastolic volume (185 ± 27 vs 165 ± 30 ml, P  = 0.02). Tricuspid ring annuloplasty effectively reduced FTR grade (3.75 ± 0.6 vs 0.3 ± 0.5, P  = 0.00004) and had little influence on RV function, cross-sectional area, radius of curvature or free wall regional strains. CONCLUSIONS: In adult sheep with 8 weeks of pulmonary artery banding and FTR, tricuspid annulus reduction of 47% with prosthetic ring annuloplasty effectively abolished FTR while maintaining regional RV function and strain patterns. Abstract : Functional tricuspid regurgitation (FTR) is commonly observed in patients with left-sided valve disease [1], and until recently, it was believed that correction of left valvular pathology would lead to resolution of tricuspid insufficiency.